Β-1, 4-endoglucanases from Talaromyces amestolkiae: Production of glucooligosaccharides from different β-glucans. Issue 1 (2nd January 2018) - de Eugenio, L. I.; Méndez-Líter, J. A.; de los Ríos, V.; Prieto, A.; Martínez, M. J.
Abstract: This article presents the purification and characterization of two β-1, 4-endoglucanases from Talaromyces amestolkiae . The cellulase activities secreted by this fungus were studied in the presence of different carbon sources, attaining the maximal levels in the presence of Avicel as carbon source. In these conditions, two glycosylated β-1, 4-endoglucanases with molecular masses of 25, 573 kDa (EG1) and 51, 825 kDa (EG2), were purified. Both isoenzymes have acidic isoelectric points, 5.4 and 4.6, respectively. Their optimum pH and temperature, either in crudes or after purification, were in the range normally used for the simultaneous saccharification and fermentation in bioethanol production. In addition, the enzymatic hydrolysis of different β-glucans by both enzymes was studied. In the assayed conditions, both enzymes hydrolysed carboxymethylcellulose, a typical substrate for endoglucanases, although EG2 was much more efficient. However, EG1 was also able to hydrolyse lichenan and laminarin. These findings suggest the potential interest of EG2 for specific hydrolysis of cellulose, present in plant cell walls, to produce bioethanol, while the more promiscuous enzyme EG1 could be used for production of glucooligosaccharides.